Fabrication and characterization of III-nitride nanophotonic devices - Dahal, Rajendra Prasad (Kansas State University, 2009)
III-nitride photonic devices such as photodetectors (PDs), light emitting diode (LEDs), solar cells and optical waveguide amplifiers were designed, fabricated and characterized. High quality AlN epilayers were grown on sapphire and n-SiC substrates by metal organic chemical vapor deposition and utilized as active DUV photonic materials for the demonstration of metal-semiconductor-metal (MSM) detectors, Schottky barrier detectors, and avalanche photodetectors (APDs). AlN DUV PDs exhibited peak responsivity at 200 nm with a very sharp cutoff wavelength at 207 nm and extremely low dark current (<10 fA), very high breakdown voltages, high responsivity, and more than four orders of DUV to UV/visible rejection ratio. AlN Schottky PDs grown on n-SiC substrates exhibited high zero bias responsivity and a thermal energy limited detectivity of about 1.0 x 1015 cm Hz1/2 W-1. The linear mode operation of AlN APDs with the shortest cutoff wavelength (210 nm) and a photocurrent multiplication of 1200 was demonstrated. A linear relationship between device size and breakdown field was observed for AlN APDs. Photovoltaic operation of InGaN solar cells in wavelengths longer than that of previous attainments was demonstrated by utilizing InxGa1−xN/GaN MQWs as the active layer. InxGa1-xN/GaN MQWs solar cells with x =0.3 exhibited open circuit voltage of about 2 V, a fill factor of about 60% and external quantum efficiency of 40% at 420 nm and 10% at 450 nm. The performance of InxGa1-xN/GaN MQWs solar cell was found to be highly correlated with the crystalline quality of the InxGa1-xN active layer. The possible causes of poorer PV characteristics for higher In content in InGaN active layer were explained. Photoluminescence excitation studies of GaN:Er and In0.06Ga0.94N:Er epilayers showed that Er emission intensity at 1.54 µm increases significantly as the excitation energy is tuned from below to above the energy bandgap of these epilayers. Current-injected 1.54 µm LEDs based on heterogeneous integration of Er-doped III-nitride epilayers with III-nitride UV LEDs were demonstrated. Optical waveguide amplifiers based on AlGaN/GaN:Er/AlGaN heterostructures was designed, fabricated, and characterized. The measured optical loss of the devices was ~3.5 cm−1 at 1.54 µm. A relative signal enhancement of about 8 dB/cm under the excitation of a broadband 365 nm nitride LED was achieved. The advantages and possible applications of 1.54 µm emitters and optical amplifiers based on Er doped III-nitrides in optical communications have been discussed.
Keywords: GaN; Photodetector; Solar cell; Optical amplifier; InGaN; Erbium; Physics, Condensed Matter (0611)